”Man börjar tänka: jaha ska jag stanna eller ska jag också gå?” : En kvalitativ studie om arbetstillfredsställelse hos socialsekreterare inom barn- och ungdomsverksamhet - Sparv,Petronella; Söderberg,Malin (2018)
“You start to wonder: should I stay or go aswell?” The purpose of this study was to examine child assistance social-workers views on work-satisfaction, and to find out what they thought mattered for accomplishing work-satisfaction. Our research questions were “How do child assistance social-workers view their work situation and their work-satisfaction?” and “What factors do child protection social-workers lift as meaningful for accomplishing work-satisfaction and what they considered that the organization contributed to their work-satisfaction?”. We gathered our empirical data through five semi-structured interviews with seven child assistance social-workers, currently working in social services in Skåne. The data was analyzed through Herzberg’s two factor theory and Hackman and Oldham's motivational theory. Our main findings were that the child assistance social-workers experienced high work-satisfaction, although they also described for example a high work-load and a demanding work situation. Our study found that different factors had an impact on work-satisfaction, among them relations within the organization, work-load, the feeling of doing something meaningful for others and visible results of their work.
Keywords: work-satisfaction; work motivation; child assistance social-workers; staff turnover; organization